Disease and Antimicrobial Resistance Surveillance for Nile Tilapia Pathogens in Lake Victoria, Kenya - Eric M. Teplitz; Venny M. Mwainge; Teresia N. Wacira; Caleb Ogwai; Meshack J. Mayianda; Linnet Ochieng; Ekta Patel; Rodman G. Getchell; Christopher M. Aura; Kathryn J. Fiorella (Journal of Fish Diseases, 2026)
The cage aquaculture industry in Lake Victoria, Kenya is growing explosively to meet increasing demand for fish, yet large‐scale fish mortalities are prevalent and pose economic shocks with catastrophic livelihood impacts. To gain a more comprehensive understanding of fish health in Lake Victoria, our study applied: (1) survey of cage farmer accounts, perceptions and responses to fish kill events; (2) rapid‐response investigation to a significant tilapia mortality event; (3) active disease surveillance; and (4) antimicrobial resistance (AMR) testing of bacterial pathogens via disk diffusion. There were 82 fish kills recalled from 2020 to 2023 with total mortalities exceeding 1.8 million tilapia; yet, only 39% of farmers reported to Kenyan institutions and 17% of farmers attempted medical treatment. Low dissolved oxygen (DO) levels and the isolation of Aeromonas jandaei , Enterobacter hormaechei and Staphylococcus epidermidis were implicated as suspected causes for a recent tilapia mortality event. Active disease surveillance detected trichodinids and monogeneans as common external parasites and identified an additional six bacterial species in tilapia ( Acinetobacter soli , Bacillus cereus , Kocuria rhizophila , Micrococcus luteus , Plesiomonas shigelloides , Staphylococcus sciuri ) previously published as fish pathogens. Furthermore, we identify AMR patterns that will support the development of host‐ and pathogen‐specific thresholds.

Investigation of round goby viral haemorrhagic septicaemia outbreak in New York - Rodman G. Getchell; Erika J. First; Steven M. Bogdanowicz; Jose A. Andrés; Adam T. Schulman; Jordan Kramer; Geofrey E. Eckerlin; John M. Farrell; Hélène Marquis (Journal of Fish Diseases, 2019)
Eleven viral haemorrhagic septicaemia virus (VHSV) genotype IVb isolates were sequenced, and their genetic variation explored to determine the source of a VHS outbreak on the eastern shore of Cayuga Lake. An active fish kill of round gobies ( Neogobius melanostomus , Pallas) was intensively sampled at King Ferry, NY and nearby Long Point State Park in May 2017. Gross lesions observed on 67 moribund round gobies and two rock bass ( Ambloplites rupestris , Rafinesque) included moderately haemorrhagic internal organs and erythematous areas on the head, flank, and fins. RT‐qPCR tests for VHSV were positive for all 69 fish. Viral isolation on epithelioma papulosum cyprinid cells showed cytopathic effect characteristic of VHSV for six round goby samples from King Ferry. The complete nucleotide sequence of the VHSV IVb genomes of five Cayuga Lake round goby isolates were derived on an Illumina platform along with 2017 VHSV IVb isolates from round gobies collected from the following: Lake Erie near Dunkirk, NY; the St. Lawrence River near Clayton and Cape Vincent, NY; and Lake St. Lawrence near Massena, NY. The phylogenetic tree created from these aligned sequences and four other complete VHSV IVb genomes shows Cayuga Lake isolates are closely related to the Lake Erie isolates.

Influence of Limnological Conditions on Clostridium Botulinum Type E Presence in Eastern Lake Erie Sediments (Great Lakes, USA) - Alicia Pérez-Fuentetaja; Mark D. Clapsadl; Donald Einhouse; Paul R. Bowser; Rodman G. Getchell; W. Theodore Lee (Hydrobiologia, 2006)